Comparison of Indonesian and Malaysian Criminal Laws in Regulating Acts of Abuse Against Minors - Sadida Amalia Izzatul Haq; Natangsa Surbakti (Universitas Muhammadiyah Surakarta, 2023)
This article is about criminal law related to child abuse. The research used is a comparative approach, ie comparing the criminal laws of the two countries based on normative legal concepts. Here is an analysis of the concept order formulation for abusive behavior against minors. In Indonesia, the Child Protection Act No. 35 of 2014 applies and in Malaysia, the Children's Act of 2001 applies. The purpose of this study is to clarify the differences and similarities between the two countries' views on child abuse regulation. The results of the two countries' basic thinking on crime and sanctions formulation are similar. In other words, it has been less than 18 years since both countries ratified their child age limit regulations, ie human rights treaties. There are some differences, such as criminal sanctions against children, punishment systems, child protection authorities, and provisions for establishing criminal offenses for child abuse. The conclusion of this article is that important to study this issue on both countries through a comparative approach that takes into account differences. Moreover, many ideas can be used to formulate abusive behavior towards minors in Indonesia.